Leading with character : stories of valor and virtue and the principles they teach - Sosik, John J. (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
What kind of character strengths must leaders develop in themselves and others to create and sustain extraordinary organizational growth and performance? In this updated and expanded second edition, the author, John J. Sosik, answers this question by reviewing what is known about the connection between authentic transformational leadership and positive psychology. He summarizes a wealth of leadership knowledge in a unique collection of captivating stories about 25 famous leaders from business, history and pop culture: Aung San Suu Kyi, John F. Kennedy, Maya Angelou, Bill Gates, Brian Wilson, Rosa Parks, Martin Luther King, Jr., Joe Namath, Malala Yousafzai, Mother Teresa, Angelina Jolie, Pope Saint John Paul II, Shirley Chisholm, Sheryl Sandberg, Andy Griffith, Margaret Thatcher, Oprah Winfrey, Nelson Mandela, Warren Buffet, Carlos Ghosn, Eleanor Roosevelt, Herb Kelleher, Steve Jobs, Johnny Cash, and Fred Rogers.What do these leaders have in common? Each possesses virtues of wisdom, courage, humanity, justice, temperance, and transcendence and their associated character strengths that form the foundation of their outstanding leadership. Besides generating astonishing results for their organizations, these leaders reaped numerous physical, mental, social and spiritual benefits from their strong character. Their stories teach readers leadership principles that they too can apply to achieve sustainable growth and excellence. The author includes dozens of interesting examples, vivid anecdotes, and clear guidelines to offer readers an in-depth look at how character and virtue forms the moral fiber of authentic transformational leadership. Individuals currently in leadership positions as well as aspiring leaders will find the book's conversational style, fascinating stories, and practical guidelines both useful and inspiring.